Pemberdayaan Masyarakat Melalui Edukasi Dan Skrining Faktor Risiko Hipertensi Di Desa Walantakan - Dian Pratiwi (AMMA : Jurnal Pengabdian Masyarakat, 2026)
Hypertension is one of the leading non-communicable diseases contributing to global morbidity and mortality. A community health survey conducted in Walantakan Village identified hypertension as a priority health problem requiring preventive and promotive interventions. This community service program aimed to improve community knowledge regarding hypertension and to conduct hypertension risk factor screening through a community empowerment approach. The program employed a Community-Based Participatory Approach, involving village authorities, primary healthcare providers, community health volunteers, and local residents. The intervention consisted of two main sessions: interactive health education using lectures, discussions, question-and-answer sessions, and educational leaflets, followed by hypertension risk factor screening through blood pressure measurement, body mass index assessment, and interviews regarding hypertension risk factors. Program evaluation was conducted using pre-test and post-test questionnaires and blood pressure screening records. The results demonstrated an increase in participants' knowledge after the educational intervention. Furthermore, blood pressure screening identified participants with elevated blood pressure, stage 1 hypertension, and stage 2 hypertension who required further medical evaluation. This community service program demonstrates that health education combined with hypertension risk factor screening is effective in improving community knowledge while facilitating early detection of hypertension to prevent cardiovascular complications.